Poetry in the mind the cognition of contemporary poetic style - Gavins, Joanna (Edinburgh University Press, 2020)
Poetry in the Mind is the first book-length cognitive analysis focused entirely on 21st century poetic texts and their conceptual effects. Addressing central poetic notions or features of poetic style from an innovative cognitive perspective, the book sheds new light on established ideas about poetic creativity and language.